Sensitivitas dan Spesifisitas Metode KOH 20% + Tinta Parker Blue Black Dibandingkan dengan KOH 20% pada Dermatomikosis Superfisialis - Firda Ulfa Ramadhani; Diana Tri Ratnasari Ratnasari; masfufatun masfufatun (Universitas Wijaya Kusuma Surabaya, 2020)
Superficial dermatomycosis is a fungal infection of the skin, nail and hair. Based on the pathogen, this infection can be divided into dermatophytosis, phytiriasis versicolor and candidiasis. The rapid diagnosis for this infection is the key point to deliver the right theraphy. The supporting investigation for this infection can be performed directly using KOH. The KOH 20% solution has an indistict color contrast, that cause the fungal element seemed transparent. The observant expertise would be required for this case. The alternative method to enhance sensitivity and specificity of KOH is to add dyes such as Blue Black parker ink. The objectives of this research was to observe the sensitivity and specificity of KOH 20% + blue black parker ink in comparisson with KOH 20% method in superficial dermatomycosis. The research method was cross sectional design analitical obsevation with 30 research subjects. The samples were taken from superficial dermatomycosis lesion swabs. These samples were tested using KOH 20% solution and KOH 20% + blue black parker ink solution in Siti Khodijah Muhammadiyah Hospital, Sepanjang and dr. Makmuri Clinics, Surabaya. The results demonstrated that the sensitivity of KOH 20% solution and KOH 20% + blue black parker ink solution were 86.67% and 93.33%, respectively. The specificity of KOH 20% solution and KOH 20% + blue black parker ink solution were 100% and 100%, respectively. It can be concluded from the research that KOH 20% + blue black parker ink solution can be used for the routine diagnosis for superficial dermatomycosis due to the high sensitivity and specificity.